ZnT-3, a putative transporter of zinc into synaptic vesicles - Palmiter, Richard D. (The National Academy of Sciences of the USA, 1996)
The murine ZnT3 gene was cloned by virtue of its homology to the ZnT2 gene, which encodes a membrane protein that facilitates sequestration of zinc in endosomal vesicles. ZnT-3 protein is predicted to have six transmembrane domains and shares 52% amino acid identity with ZnT-2, with the homology extending throughout the two sequences. Human ZnT-3 cDNAs were also cloned; the amino acid sequence is 86% identical to murine ZnT-3. The mouse ZnT3 gene has 8 exons and maps to chromosome 5. Northern blot and reverse transcriptase–PCR analyses demonstrate that murine ZnT-3 expression is restricted to the brain and testis. In situ hybridization reveals that within the brain, ZnT-3 mRNA is most abundant in the hippocampus and cerebral cortex. Antibodies raised against the C-terminal tail of mouse ZnT-3 react with the projections from these neurons and produce a pattern similar to that obtained with Timm’s reaction, which reveals histochemically reactive zinc within synaptic vesicles. We propose that ZnT-3 facilitates the accumulation of zinc in synaptic vesicles.